An assessment of postural sway in ballet dancers during first position, relevé and sauté with accelerometers - Hinton-Lewis, C. W.; McDonough, E.; Moyle, G. M.; Thiel, D. V. (Procedia Engineering, 2016)
Classical ballet is a performance art where unintentional and uncontrolled movement degrades the aesthetic. Vertical torso movement can induce body tilt. Postural sway was measured in pre-professional ballet dancers when performing simple vertical movements. 47 pre-professional dancers (5 males and 42 females, mean age in years = 19.2, SD= 1.3) on a full time undergraduate dance program were asked to stand in first position and perform a demi-plié, a relevé and a sauté. These movements were performed in a continuous cycle undertaken 15 consecutive times. The first 5 cycles were undertaken as practice. The second set of 5 cycles were recorded with the arms held in Bras bas, with the final 5 having the arms held in fifth position (rounded arms placed above the head). Accelerometers were attached to the lumber spine (L4) and thoracic spine (T1-T2). The tilt during the demi-plié prior to the sauté and relevé increased significantly for both arm positions. The male participants preparative angle change was much larger than the female participants (p = 0.07). No significant angle change was observed between the Bras bas and arms in fifth position for the sauté but the change is significant for the relevé (p = 0.007). Exaggerated forward tilt is undesirable both aesthetically and biomechanically. Small accelerometer sensors on the spine can allow self-monitoring practice of these basic classical ballet movements.